Primary cutaneous anaplastic large cell lymphoma with lung metastasis - Esa, Nor Kamaruzaman; Abdullah, Kahairi; Abdul Rasheed, Shamim Rahman (School of Dental Sciences, 2016)
Primary cutaneous anaplastic large cell lymphoma (PC-ALCL) is relatively a rare tumour of head and neck region. Without histopathological confirmation, it appears and behaved as like malignant epithelial tumor of the head and neck region as will be illustrated in the present case. Cutaneous involvement of the tumor with distant metastasis has made the prognosis unfavorable. This isolated case of head and neck PC-ALCL was highlighted as it has a tendency to behave aggressively and early diagnosis and treatment is crucial to avoid poor survival outcome.